Reproductive Biology of Featherback Fish (Notopterus notopterus Pallas, 1769) from the Sail River, Pekanbaru Regency, Riau Province - Rizki, Aisya Ayu; Efizon, Deni; Putra, Ridwan Manda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Featherback fish (Notopterus notopterus) is a type of freshwater fish that inhabit the Sail River, Riau Province. To understand the reproductive biology of this fish, a study has been conducted from March to April 2017. Total fish captured was 70 (34 males and 36 females). Sex ratio between male and female was 1 : 1. The gonado somatic index (GSI) of the male was 0.06-0.78 % and that of the female was 0.05%-6.78%. The fecundity of the fish were 1.630-5.526 eggs/fish. Egg diameter was 1.8 mm-2.5 mm. The relationship between fecundity and standard lenght was y = 3.11x - 4.06, that of the fecundity and body weight was y = 1.86x-0.86, and that of the fecundity and ovary weight was y = 0.81x+2.66. The water quality parameter are as follows : temperature 28-300C, transparency 5.5-15.5 cm, depth 0.7-1.87 cm, pH 6, DO 2.4-4 mg/L, and CO2 11.9-19.9 mg/L.Keyword : Notopterus notopterus, Sail River, GSI, fecundity, and eggs diameter